A Novel Flavi-like Virus in Alfalfa (Medicago sativa L.) Crops along the Snake River Valley - Jennifer Dahan; Yuri I. Wolf; Gardenia E. Orellana; Erik J. Wenninger; Eugene V. Koonin; Alexander V. Karasev (Viruses, 2022)
Alfalfa is an important perennial forage crop in Idaho supporting dairy and cattle industries that is typically grown in the same field for as many as 4 years. Alfalfa stands of different ages were subjected to screening for viruses using high-throughput sequencing and RT-PCR. The two most common viruses found were alfalfa mosaic virus and bean leafroll virus, along with Medicago sativa amalgavirus, two alphapartitiviruses, and one deltapartitivirus. Additionally, a new flavi-like virus with an unusual genome organization was discovered, dubbed Snake River alfalfa virus (SRAV). The 11,745 nt, positive-sense (+) RNA genome of SRAV encodes a single 3835 aa polyprotein with only two identifiable conserved domains, an RNA-dependent RNA polymerase (RdRP) and a predicted serine protease. Notably, unlike all +RNA virus genomes in the similar size range, the SRAV polyprotein contained no predicted helicase domain. In the RdRP phylogeny, SRAV was placed inside the flavi-like lineage as a sister clade to a branch consisting of hepaci-, and pegiviruses. To the best of our knowledge, SRAV is the first flavi-like virus identified in a plant host. Although commonly detected in alfalfa crops in southern Idaho, SRAV sequences were also amplified from thrips feeding in alfalfa stands in the area, suggesting a possible role of Frankliniella occidentalis in virus transmission.